HSP70 of Leishmania amazonensis alters resistance to different stresses and mitochondrial bioenergetics - Bárbara Santoni Codonho; Solange dos Santos Costa; Eduardo de Figueiredo Peloso; Paulo Pinto Joazeiro; Fernanda Ramos Gadelha; Selma Giorgio (Memorias do Instituto Oswaldo Cruz, 2016)
The 70 kDa heat shock protein (HSP70) is a molecular chaperone that assists the parasite Leishmania in returning to homeostasis after being subjected to different types of stress during its life cycle. In the present study, we evaluated the effects of HSP70 transfection of L. amazonensis promastigotes (pTEX-HSP70) in terms of morphology, resistance, infectivity and mitochondrial bioenergetics. The pTEX-HSP70 promastigotes showed no ultrastructural morphological changes compared to control parasites. Interestingly, the pTEX-HSP70 promastigotes are resistant to heat shock, H2O2-induced oxidative stress and hyperbaric environments. Regarding the bioenergetics parameters, the pTEX-HSP70 parasites had higher respiratory rates and released less H2O2 than the control parasites. Nevertheless, the infectivity capacity of the parasites did not change, as verified by the infection of murine peritoneal macrophages and human macrophages, as well as the infection of BALB/c mice. Together, these results indicate that the overexpression of HSP70 protects L. amazonensis from stress, but does not interfere with its infective capacity.